Low power laser radiation at 685 nm stimulates stem-cell proliferation rate in Dugesia tigrina during regeneration - de Souza, S. C.; Munin, E.; Alves, L. P.; Salgado, MAC; Pacheco, MTT (Elsevier B.V., 2005)
Today's scientific interest in tissue engineering for organ transplantations and regeneration from stem cells, allied with recent observations on biostimulation of tissues and cells by laser radiation, stands as a strong motivation for the present work, in which we examine the effects of the low power laser radiation onto planarians under regenerative process. To investigate those effects, a number of 60 amputated worms were divided in three study groups: a control group and two other groups submitted to daily 1 and 3 min long laser treatment sections at similar to 910 W/m(2) power density. A 685 nm diode laser with 35 mW optical power was used. Samples were sent to histological analysis at the 4th, the 7th and the 15th (lays after amputation. A remarkable increase in stem cells counts for the fourth day of regeneration was observed when the regenerating worms was stimulated by the laser radiation. Our findings encourage further research works on the influence of optical radiation onto stem cells and tissue regeneration. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: neoblast; wound healing; laser therapy; photobiomodulation; flatworms; Planaria